By using the definition of the equation of the line, the canonical form of the equation 2 · y - 8 · x + 3 = 0 is equivalent to - 8 · x + 2 · y = - 3.
In this problem we have the equation of the line in a non-canonical form. The canonical form of the equation of the line is described below:
A · x + B · y = C (1)
Where:
Then, we proceed to modify the expression given by algebraic handling:
2 · y - 8 · x + 3 = 0
2 · y - 8 · x = - 3
- 8 · x + 2 · y = - 3
By using the definition of the equation of the line, the canonical form of the equation 2 · y - 8 · x + 3 = 0 is equivalent to - 8 · x + 2 · y = - 3.
To learn more on equations of the line: https://brainly.com/question/14200719
#SPJ1